The Influence of Financial Ratios and Firm Size on Stock Return - Romantica , Krishna Prafidya; Jalaludin, Paiz (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Researchers analyze financial ratio data using a quantitative approach to determine the effect on the company's stock return. Researchers formulated four research hypotheses. The data will be modeled using the Panel Data Regression method with the help of E-Views 12 Student software. With purposive sampling techniques, researchers will use stock closing price data and financial statements from 9 Properties and Real Estate companies listed on the Indonesia Stock Exchange (period 2018 to 2022). With the chow test and lagrange multiplier test, researchers will model the data using a common effect model. The results showed that the ROA of der, CR, and FS, either simultaneously or partially, did not have a significant effect on stock returns. Based on signal theory, capital owners will receive bad signals from the company because the variables ROA, DER, CR, FS are considered unable to influence the company's stock return.